COMPARATIVE ANALYSIS OF PHYSIOLOGICAL RESPONSES OF POTATO SEEDLINGS TO OSMOTIC STRESS OF DIFFERENT INTENSITIES - Argumbayeva , A.K.; Kali , B.R.; Abeuova , L.S.; Nasiyev , B.N.; Manabayeva , S.A. (Eurasian Journal of Applied Biotechnology, 2025)
Drought is one of the most significant abiotic stresses that limit plant growth and crop productivity. This study analyzed the physiological responses of potato (Solanum tuberosum L.) seedlings to osmotic stress induced by polyethylene glycol (PEG-6000) at concentrations of 0, 2, 4, 6, and 8%. High concentrations of PEG-6000 were found to significantly inhibit seedling growth and reduc chlorophyll content. Physiological analysis revealed decreased in malondialdehyde (MDA) levels and increased catalase (CAT) activity under osmotic stress conditions. These results deepen our understanding of the physiological processes and internal mechanisms of potato drought tolerance, including changes in chlorophyll content. This knowledge can be applied to breeding programs that develop cultivars resistant to abiotic stresses.